CONCERNING MARINA TSVETAEVA’S CREATIVE WORKBOOKS. - GEVORKYAN, TATYANA (Bulletin of Yerevan University H: Russian Philology, 2019)
The paper presents the results of the work on the publication of materials from Marina Tsvetaeva’s archive, available at the moment. It is focused on the last (1918) valuable scientific edition of the draft workbooks having a fundamental importance for the research of the poetess’s creation, as well as the comprehension of her creative process. The mentioned edition in 2 volumes presents draft workbooks from 1919 and 1919-1921, with the prospect of making it the first part of “Creative Workbooks” project which shall gather materials from different phases of creation. The author brings convincing examples from her own experience, highlighting how the information contained in workbooks contributes to research.